Answer:
4x² - x - 1
Step-by-step explanation:
(f - g)(x) = f(x) - g(x) , thus
f(x) - g(x)
= 4x² - (x + 1) ← distribute parenthesis by - 1
= 4x² - x - 1
72/4 = 18 (18)(2/3) = 12. The answer is $12.00 per hour
Check the slope between the moving points
<span>slope between (–6, –1) & (–3, 2) = 1 </span>
<span>slope between (-3, 2) & (–1, 4) = 1 </span>
<span>slope between (-1, 4) & (2, 7) = 1 </span>
<span>the points are collinear and make an angle of 45 degrees with the x-axis </span>
<span>we can have an equation of a line passing through (-6,-1) and slope 1 as </span>
<span>(y + 1) = 1(x + 6) </span>
<span>y = x + 5 is your linear model mostly</span>
Answer:
Step-by-step explanation:
The sum of the interior angles, in degrees, of a regular polygon is given by the formula 180(n – 2), where n is the number of sides. The problem concerns a polygon with six sides, so we will let n = 6. The sum of the interior angles in this polygon would be 180(6 – 2) = 180(4) = 720. The angle on the bottom left is a right angle because of the square indicator. We know that this is 90 degrees. If we take the sum of the angles that we know we get 593. 720 - 593 = 127. x = 127.
Answer:
11
Step-by-step explanation:
Angle SRT + angle RTU = angle STU
11x - 7 + 2x + 16 = 152 add like terms
13x + 9 = 152
13x = 143
x = 11